Affluence Putting Health Of Malaysians At Risk - New Sunday Times, (2008)
Blame it on metabolic disorders. Health Ministry statistic show that diabetes is today a common Malaysian malaise while coronary artery disease and obesity rates are reaching alarming levels, even among the young.